Practical realization of organizational and methodical system education of bilingual culture for future teachers of foreign language - Дьоміна, В. В. (Scientific notes of the pedagogical department, 2018)
The aim of the article is illumination of questions of practical realization of the organizationally-methodical system of education of bilingual culture for the future teachers of foreign language in integral educationally-educator process of higher pedagogical educational establishment.In basis of the organization and methodological system of education of bilingual culture for the future teachers of foreign language the idea of system development is fixed for the students of all of the tools of bilingual culture (knowledge, cross-cultural communicative competense, communicative abilities,  culture skills). By means of application of complex of methods, forms and facilities of pedagogical influence on personality, adapted to the educational process in higher pedagogical educational establishments, students seize certain linguistic and culturological knowledge about factors, that assist forming in them them bilingual consciousness, linguistic knowledge, culture of speech, culture, moral qualities, aesthetic taste and active vital position.Thus, introduction of the organizationally-methodical system of education of bilingual culture for the future teachers of foreign language provides quality of educationally-educator process pedagogical hang, the address of all of the tools of education promotes to the man as subject of culture, apt at permanent self development her professional culture of teacher-philologist as difficult complex of sociocultural, linguistic, culturological knowledge, abilities, qualities and capabilities that provide socialization and cultural integration of personality in modern multicultural space. organizationally-methodical system of education of bilingual culture for the future teachers of foreign language assists education of bilingual culture of teachers and provides social adaptation and self-affirmation of personality of future teacher of foreign language in the multicultural environment of modern educational space; prepares students to ability to conduct the dialogue of cultures with the representatives of other nations, understanding them in a civilized manner-speech specific.